OPTIMALISASI KETERAMPILAN BERBAHASA INDONESIA DENGAN PROJECT-BASED LEARNING DI UPT SDN KADINGDING - Niky Desta Amini; Andini Suci Anggraeni; Desty Endrawati Subroto (Jurnal Padamu Negeri, 2025)
This research aims to explore how implementing a project-based learning model can improve students' Indonesian language skills. With a more active and collaborative approach, it is hoped that students will not only master technical language skills, but can also apply them in a wider social and cultural context. This research aims to explore how implementing a project-based learning model can improve students' Indonesian language skills. With a more active and collaborative approach, it is hoped that students will not only master technical language skills, but can also apply them in a wider social and cultural context..This learning approach emphasizes students' active participation in designing, implementing, and presenting projects as a way to develop their knowledge and skills. The method used in this research is classroom action research (PTK) which is carried out in two cycles, each of which includes planning, implementation, and evaluation. The subjects in this research were fifth grade students at UPT SDN KADINGDING school year 2024/2025. The research results showed that the application of the project-based learning model was successful in improving students' Indonesian language skills, including speaking, writing, listening and reading skills. Students also show significant increases in motivation, creativity, and communication skills through the projects they undertake. Thus, the project-based learning model can be an effective choice for improving students' Indonesian language skills.